Direct Spectrophotometric Determination of Glimepiride in Pure Form And Pharmaceutical Formulations Using Bromocresol Purple (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
A simple, direct and accurate spectrophotometric method has been developed for the determination of Glimepiride (GLM) in pure and pharmaceutical formulations by complex formation with bromocresol purple (BCP). The method involves the formation of a yellow ion-pair complex between BCP with glimepiride at pH